OTORITAS PEMERINTAH DALAM PENETAPAN AWAL BULAN QAMARIYAH PERSPEKTIF FIQH SIYÂSAH YUSUF QARDHAWI. - Hidayat, M. Nur (Fakultas Syariah, 2012)
The disparity of determining the early month of Qamariyah in Indonesia is a common phenomenon every year. Therefore, the government, through Ministry of Religious Affairs tries to find a solution for the problem. The focus of this study is to discuss the government’s authority in determining the early month of Qamariyah based on Yusuf Qardhawi’s Political Fiqh Perspective. As a result, the study shows that the government, the Ministry of Religious Affairs of Indonesia, has an authority in determining the early month of Qamariyah. Meanwhile, Islamic organizations or other mass organizations have no authority at all. But, they deserve in announcing after receiving the information from government. Furthermore, the government’s decision is considered as an obligation which has to be obeyed for those having no ability in determining the early month of Qamariyah (independent-ijtihad). Perbedaan penetapan awal bulan Qamariyah di Indonesia menjadi sebuah fenomena dalam setiap tahun. Guna menjembatani perbedaan tersebut, pemerintah mengambil langkah solutif untuk menyelesaikan permasalahan tersebut. Fokus penelitian ini adalah untuk mendiskusikan otoritas pemerintah dalam penetapan awal bulan Qamariyah perspektif fiqh siyâsah Yusuf Qardhawi. Dari hasil penelitian, diperoleh kesimpulan bahwa pemerintah dalam hal ini Kementerian Agama RI mempunyai otoritas dalam menetapkan (itsbât) awal bulan Qamariyah. Sedangkan organisasi ataupun ormas Islam di luar pemerintah pada hakikatnya tidak mempunyai otoritas dalam menetapkan awal bulan Qamariyah, akan tetapi hanya sekedar mengumumkan (ikhbâr) terkait dengan awal bulan qamariyah. Selanjutnya mengenai keputusan pemerintah, pada dasarnya wajib diikuti bagi mereka yang tidak mempunyai kemampuan untuk melakukan ijtihad sendiri dalam menentukan awal bulan Qamariyah.